Interlayer bonding between thermoplastic composites and metals by in‐situ polymerization technique. Issue 40 (29th May 2021) - Robert, Colin; Mamalis, Dimitrios; Obande, Winifred; Koutsos, Vasileios; Ó Brádaigh, Conchúr M.; Ray, Dipa
Abstract: Fiber‐metal laminates (FMLs) offer the superior characteristics of polymer composites (i.e., light weight, high strength and stiffness) with the ductility and fracture strength of metals. The bond strength between the two dissimilar materials, composite and metal, dictates the properties and performance of the FMLs. The bonding becomes more critical when the polymer matrix is thermoplastic and hydrophobic in nature. This work employed a novel bonding technique between thermoplastic composites and a metal layer using six different combinations of organic coatings. The flexural, and interlaminar shear strength of the thermoplastic fiber metal laminates (TP‐FMLs) were examined to investigate the bond strengths in the different cases along with fracture characteristics revealed from the tested samples using scanning electron microscopy. The viscoelastic performance of the fabricated TP‐FMLs were also investigated using the dynamic mechanical thermal analysis method. Abstract :